2011
DOI: 10.1007/s11104-010-0691-9
|View full text |Cite
|
Sign up to set email alerts
|

13C isotope fractionation during rhizosphere respiration of C3 and C4 plants

Abstract: Stable carbon isotopes are used extensively to partition total soil CO 2 efflux into root-derived rhizosphere respiration or autotrophic respiration and soil-derived heterotrophic respiration. However, it remains unclear whether CO 2 from rhizosphere respiration has the same δ 13 C value as root biomass. Here we investigated the magnitude of 13 C isotope fractionation during rhizosphere respiration relative to root biomass in six plant species. Plants were grown in a carbon-free sand-perlite medium inoculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…In earlier studies at the Niwot Ridge forest, we found that nocturnal δ R on a nightly basis tended to be more enriched within the vegetation canopy relative to near the ground [ Bowling et al , ; Riveros‐Iregui et al , ]. This is qualitatively consistent with plant‐scale observations of relatively enriched foliar respiration [ Bowling et al , ; Wingate et al , ] and relatively depleted root respiration [ Ghashghaie and Badeck , ; Schnyder and Lattanzi , ; Zhu and Cheng , ]. These results complicate the simple conceptual model we have used (equations –) and suggest that more complex biophysical models [ Baldocchi and Bowling , ; Flanagan et al , ; Wingate et al , ] combined with flux and isotopic flux observations from different ecosystem pools are likely the best way to investigate the isotopic composition of the photosynthesis and respiratory fluxes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In earlier studies at the Niwot Ridge forest, we found that nocturnal δ R on a nightly basis tended to be more enriched within the vegetation canopy relative to near the ground [ Bowling et al , ; Riveros‐Iregui et al , ]. This is qualitatively consistent with plant‐scale observations of relatively enriched foliar respiration [ Bowling et al , ; Wingate et al , ] and relatively depleted root respiration [ Ghashghaie and Badeck , ; Schnyder and Lattanzi , ; Zhu and Cheng , ]. These results complicate the simple conceptual model we have used (equations –) and suggest that more complex biophysical models [ Baldocchi and Bowling , ; Flanagan et al , ; Wingate et al , ] combined with flux and isotopic flux observations from different ecosystem pools are likely the best way to investigate the isotopic composition of the photosynthesis and respiratory fluxes.…”
Section: Discussionsupporting
confidence: 87%
“…As carbon is transferred from plant pools to other ecosystem pools through herbivory, root exudation, and mortality, there are additional fractionations but most of them are poorly understood. These effects all combine to influence the δ 13 C of leaf, root, and heterotrophic respiration in complex ways [ Barbour et al , ; Brüggemann et al , ; Werner and Gessler , ; Zhu and Cheng , ]. In earlier studies at the Niwot Ridge forest, we found that nocturnal δ R on a nightly basis tended to be more enriched within the vegetation canopy relative to near the ground [ Bowling et al , ; Riveros‐Iregui et al , ].…”
Section: Discussionmentioning
confidence: 67%
“…Path [2] is refixation of carbon from root respiration. According to Zhu and Cheng (), Amaranthus tricolor root respiration showed a Δ of +7‰. Based on this value and our root biomass 13 C content (Table ), we calculate a δ 13 C value of the respired CO 2 to be around −24‰.…”
Section: Resultsmentioning
confidence: 81%
“…where d 13 C root is the d 13 C value of rhizosphere respiration which was calculated based on the d 13 C value of shoot biomass and the 13 C fractionation of root-derived CO 2 relative to shoot biomass (1.1& for sunflower and 1.3& for soybean, Zhu and Cheng, 2011b).…”
Section: Measurements and Calculationsmentioning
confidence: 99%